Low flow season river discharge boundaries definition of Greek rivers to assess the impact of hydrometeorological and climatic pressures - Angeliki Mentzafou; Elias Dimitriou; Anastasios Papadopoulos; Petros Katsafados (Hydrological Sciences Journal, 2026)

Investigating the impact of sea surface temperature on the development of the Mediterranean tropical-like cyclone “Ianos” in 2020 - George Varlas; Ioannis Pytharoulis; Gert-Jan Steeneveld; Petros Katsafados; Anastasios Papadopoulos (Atmospheric Research, 2023)

The Hellenic Marine Observing, Forecasting and Technology System—An Integrated Infrastructure for Marine Research - Evi Bourma; Leonidas Perivoliotis; George Petihakis; Gerasimos Korres; Constantin Frangoulis; Dionysios Ballas; Vassilis Zervakis; Elina Tragou; Petros Katsafados; Christos Spyrou; Manos Dassenakis; Serafim Poulos; et al. (Journal of Marine Science and Engineering, 2022)
Research infrastructures have been established throughout Europe in order to create robust organizations that will facilitate and enhance research and innovation processes and will advance society with innovative products and services. The Hellenic Integrated Marine Observing, Forecasting and Technology System (component of HIMIOFoTS RI) has been implemented in the framework of the National Roadmap for Research Infrastructures to form a large-scale infrastructure for the marine environment in Greece. It links together ocean observing and forecasting systems, coastal zone monitoring and management practices, as well as ocean engineering testing facilities. The overarching framework of the system supports the coordination of five organizations with expertise in the field of marine science and technology, the central management of research activities, and the common development of services and products. It comprises facilities and resources while it provides open access to research communities (academia, industry) to support the scientific advancements and innovation in their fields. The Hellenic Marine Observing, Forecasting and Technology System was further enhanced during its implementation through significant upgrades and developments in order to extend its observing capacity and the forecasting and technological abilities, while advancing the provided services and products.

One-year assessment of the two-way coupled atmosphere-ocean wave modeling system CHAOS over the Mediterranean and Black Seas - GEORGE VARLAS; CHRISTOS SPYROU; ANASTASIOS PAPADOPOULOS; GERASIMOS KORRES; PETROS KATSAFADOS (Mediterranean Marine Science, 2020)
Nowadays, it has become clear that atmosphere and ocean should be simulated by integrated modeling systems resolving interconnected physical factors which determine Earth’s energy balance. Waves play a key role on the interfacial interaction between atmosphere and ocean regulating momentum, heat and moisture exchange. This study aims to evaluate the two-way coupled atmosphere-ocean wave system CHAOS (Chemical Hydrological Atmosphere Ocean wave System) over the Mediterranean and Black Seas. The evaluation is performed against in-situ and remote sensing data for the period from 1 December 2013 to 1 December 2014. CHAOS includes the Weather Research Forecasting (WRF) model version 3.8 as atmospheric component and the Wave model (WAM) cycle 4.5.4 as ocean wave component, coupled through the OASIS3-MCT coupler version 3.0. In order to assess the impact of the atmosphere-ocean waves coupling, two approaches of continuous model simulations are followed. In the first approach (1-way coupling mode) the ocean wave component uses the winds produced by the atmospheric component while in the second approach (2-way coupling mode) the atmospheric component additionally uses the sea state information estimated by the ocean wave component through wave-dependent Charnock parameter computations. In the 2-way coupling mode, the attenuation of the atmospheric flow has a damping effect on wind-generated waves. The simulations in 2-way coupling mode produce more realistic results yielding statistical improvements. Against buoys observations, 2-way reduces root mean square error (RMSE) per 1.2% and 6.3% for wind speed and significant wave height, respectively, while against Jason-2 satellite retrievals per 0.5% and 2.4%, respectively. Additionally, the 2-way outperforms the 1-way coupling mode under intense wind and wave conditions during this one-year period.

Assessing the impact of Argo floats temperature measurements on the numerical weather prediction forecast skill - GEORGE VARLAS; PETROS KATSAFADOS; GERASIMOS KORRES; ANASTASIOS PAPADOPOULOS (Mediterranean Marine Science, 2019)
The forecast skill of numerical weather prediction (NWP) models relies, among other factors such as the prediction itself and the assimilation scheme, on the accuracy of the observations utilized in the assimilation systems for the production of initial and boundary conditions. One of the most crucial parameters in weather forecasting is the sea surface temperature (SST). In the majority of NWP models, the initial and lower boundary conditions involve gridded (SST) analyses which consist of data obtained by buoys, ships and satellites. The main aim of this study is to integrate Argo temperature measurements in gridded SST analyses and to assess their impact on the forecast skill of a limited area atmospheric model. Argo floats are “state-of-the-art” oceanographic instruments producing high-quality temperature profiles for the ice-free ocean. In this study, Argo temperatures are incorporated into gridded SST fields without applying any smoothing method in order to directly assess the impact of Argo temperatures on numerical weather prediction. Their impact is assessed under intense weather cyclonic conditions at the Mediterranean Sea by performing two sensitivity simulations either incorporating or not Argo temperatures into gridded SST fields used in the generation of the initial and lower boundary conditions. The results indicate that the inclusion of Argo-measured near-surface temperatures in the lower boundary condition modifies the surface heat fluxes, thus affecting mean sea level pressure and precipitation. In particular, an overall improvement of the precipitation forecast skill up to 3% has been demonstrated. Moreover, the incorporation of Argo temperatures affects the simulated track and intensity of the cyclone over the Balkan Peninsula.

An analysis of the synoptic and dynamical characteristics of hurricane Sandy (2012) - George Varlas; Anastasios Papadopoulos; Petros Katsafados (Meteorology and Atmospheric Physics, 2019)

Investigation of flash flood natural causes of Xirolaki Torrent, Northern Greece based on GIS modeling and geomorphological analysis - Konstantinos Tsanakas; Kalliopi Gaki-Papanastassiou; Kleomenis Kalogeropoulos; Christos Chalkias; Petros Katsafados; Efthimios Karymbalis (Natural Hazards, 2016)